Standardized Measurement of Muscle Strength and Physical Performance for Sarcopenia: An Expert-Based Delphi Consensus - Seung-Kyu Lim; Jaewon Beom; Sang Yoon Lee; Kyunghoon Min; Seong-Eun Byun; Yonghan Cha; Jun Hwan Choi; Jung-Yeon Choi; Jae-Young Han; Hak-Chul Jang; Hee-Won Jung; Kwang-Il Kim; et al. (Annals of Geriatric Medicine and Research, 2025)
Background Despite updated sarcopenia guidelines, inconsistent protocols still cause clinical confusion and may compromise diagnostic and outcome accuracy. This Delphi study aimed to establish expert consensus to support the standardization of muscle strength and physical performance assessments for sarcopenia. Methods A two-round modified Delphi study was conducted with 26 experts in geriatrics and sarcopenia. Participants completed two rounds of anonymous questionnaires evaluating 39 items across seven domains using a nine-point Likert scale or choice-based questions. Consensus was defined as ≥75% agreement. Results In total, 27 of 38 statements (71.1%) reached consensus across two rounds Experts supported further standardization of assessments in alignment with the Asian and Korean Working Group on Sarcopenia (AWGS and KWGS) guidelines. For handgrip strength, consensus was achieved on using both mechanical and hydraulic dynamometers, hydraulic protocols, value selection, measurement time, and positioning, but not on mechanical protocols, repetitions, recovery intervals, repetitions, or unified cutoff values. For calf circumference, consensus was reached on measurement position, method, and value selection, but not on guideline application. In gait speed assessment, agreement was reached on speed, repetitions, assistive device use, and equipment type, but not on value selection, distance, acceleration/deceleration phases, or device interchangeability. For the 400-m walk test, the KWGS guideline and speed were endorsed. Chair stand test (CST) and Timed up-and-go (TUG) test reached consensus on armrest use, value selection, and repetitions, but not on seat height, (CST), or speed (TUG). Conclusion This study highlights areas of agreement and ongoing uncertainty, supporting future standardization efforts sarcopenia assessment methods.